Peace at Last Sight': The Other Face of Warchitecture' - Saifi, Yara; Hurol, Yonca (Mdpi, 2018)
The first part of the title of this article purposefully recalls Walter Benjamin's interpretation of love at last sight' in connection with Charles Baudelaire's famous poem entitled To a Passerby' in his famous book The Flowers of Evil'. The poem was written about a lost chance of love. Within the title of this article it is used in relation to the concept of peace. The other part of the title contains Andrew Herscher's concept of warchitecture', which is used to describe destroyed or semi destroyed pieces of architecture in political conflict zones. The paper intendeds to represent another face of warchitecture, which has nothing to do with physical destruction. By making value judgements regarding examples of architectural aesthetics, which exist within a long-term conflict zoneJerusalem; Mosche Safdie's David Village and Santiago Calatrava's Bridge of Strings will be discussed. Peacefully they may stand in their appearance, they express a nonbeing peace' when analyzed in relation to their context. Accordingly, this paper questions both buildings' attempts to peace and harmony when discrimination is taking place against Palestinians in Jerusalem. By articulating the relationship between the representation of nonbeing' and the destruction of buildings' warchitecture' during wars, the paper shows that neglect can be another tool of destruction towards Palestinians and their culture.
Keywords: warchitecture; architectural aesthetics; peace; Jerusalem